The Kalahari Desert Festival: Music and Dance as a Celebration of Heritage and Identity Amongst the ǂKhomani San - Adams, Eshcha (College of Music, 2024)
The Kalahari Desert Festival is a significant annual festival, which provides a platform for local ǂKhomani San and related regional communities to celebrate their heritage and identity through music, dance and other art forms. Held on indigenous lands in South Africa's Northern Cape Province, I discuss how the festival emerged as an important site of San cultural sustainability and appreciation since its establishment in 2013. To contextualise my discussion, I discuss the various ways indigenous people in southern Africa have been historically marginalised as a direct cause of colonialism and apartheid, and the subsequent scholarship on various San cultural practices including music and language, which have disproportionately been framed through dominant western scholarship. Within this context, I explore emerging decolonial scholarly literature and approaches which have been undertaken by black, indigenous and people of colour (BIPOC) scholars in South Africa. By employing a method of historical reconstruction gleaned from interviews, proposals, news articles, footage and in-person experience at the Kalahari Desert Festival, I provide a detailed historical outline of the festival during its seven-year run between 2013–2019. Furthermore, I position the festival as a platform and catalyst for the celebration of heritage and identity, highlighting the significance of a cultural festival which is geographically ‘on the margins', by intentionally centring historically marginalised people. By presenting several emerging concepts and themes centred around cultural sustainability, I discuss how the festival can be seen as a catalytic space which promotes heritage and identity in various symbolic ways – helping local communities claim dignity, pride and agency towards self-determination as indigenous people within a post-apartheid socio-political South African climate. The Kalahari Desert Festival has, until my current discussion, never been the focus of any academic research studies. Being relatively new, I believe it is a significant research focal point, as I explore ideas of heritage, identity, cultural sustainability and artistic expression amongst the ǂKhomani San and beyond.